Proceedings of the 22nd ACM International Conference on Information &Amp; Knowledge Management 2013
DOI: 10.1145/2505515.2505679
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of web-search using short-term browsing context

Abstract: Search and browsing activity is known to be a valuable source of information about user's search intent. It is extensively utilized by most of modern search engines to improve ranking by constructing certain ranking features as well as by personalizing search. Personalization aims at two major goals: extraction of stable preferences of a user and specification and disambiguation of the current query. The common way to approach these problems is to extract information from user's search and browsing long-term h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…• Short-term history: the user past interactions with the system in the current search session [142,143,144].…”
Section: Learning With Contextmentioning
confidence: 99%
“…• Short-term history: the user past interactions with the system in the current search session [142,143,144].…”
Section: Learning With Contextmentioning
confidence: 99%
“…It involves two important problems, namely, how to determine the duration of a session and how to learn the user preference in a session. To solve these problems, Sriram et al [55] used temporal closeness and probabilistic similarities between queries to determine the duration of a session; Daoud et al [14,15] leveraged a predefined ontology of semantic concepts to construct the short-term user profile; methods in [58,61] determine the extent of using context (e.g., prior queries and clicks) and investigate the combination of the query and the context to model the user intention; and Shen et al [52] captured users' interests by analyzing the immediate contexts and implicit feedback.…”
Section: Personalized Web Searchmentioning
confidence: 99%
“…Besides search behaviors in one search session (instant and short term), research has also considered search history in previous sessions (long term) (e.g., Albanese, Picariello, Sansone, & Sansone, 2004;Sontag et al, 2012;Ustinovskiy & Serdyukov, 2013;Wedig & Madani, 2006). Regarding the usefulness of short-and long-term behaviors for personalization, Zhu, Callan, and Carbonell (2008) found that incorporating short-term contexts works well for personalized search, and longer history does not provide further improvement.…”
Section: Rlb Personalization Using Search Behaviorsmentioning
confidence: 99%